Experimental Study on Physical Similar Model of Fault Activation Law Based on Distributed Optical Fiber Monitoring - Dingding Zhang; Yanyan Duan; Wengang Du; Jing Chai (Shock and Vibration)
The impact ground pressure in coal mining is closely related to the fault structure, and the fault activation pattern is different when the working face advances along the upper and lower plates of the fault, respectively. In this paper, the F16 positive fault in the southern part of Yima coalfield is used as a prototype to carry out the physical similar model test simulating the process of the working face advancing from the upper and lower plates of the fault, and PPP-BOTDA optical fiber sensing technique is used to study the overburden deformation law and fault activation law when the working face is located in the upper and lower plates of the fault, respectively. The study shows that the key stratum breakage is closely related to the fault movement, and the shear stress concentration range occurs within the key stratum. The additional shear stress concentration at the fault surface caused by the working face advancing in the lower plate is much larger than that at the upper plate, which is the reason for the serious fault destabilization phenomenon at the lower plate. The upper rock layer on the fault face is affected by the mining action of the working face before the lower one, and the working face is affected by the fault in a larger range when advances in the lower plate than that in the upper plate, and the risk of fault activation instability occurs earlier when the working face advances in the lower plate than that in the upper plate. The distributed optical fiber sensing technology is used to verify the basic conclusions that the impact of the working face advancing from the lower plate is much greater than that from the upper plate, which is more likely to cause fault activation. The preferential placement of the working face in the upper plate in the fault area will be beneficial to mine pressure control. The results of the study provide an experimental basis for the application of distributed optical fiber sensing technology to the study of fault activation law.